Attitude in learning physics among form four students / Norezan Ibrahim, Mohd Aiman A. Zakiang and Siti Maftuhah Damio - Ibrahim, Norezan; A. Zakiang, Mohd Aiman; Damio, Siti Maftuhah (Research Management Centre (RMC), 2019)
ABSTRACT Physics is considered as the most challenging area of learning within the field ofscience, and it usually magnetisesfewerstudents compared to other science related subjects from secondary school to university. Generally, students tend to have a negative attitude towards physics presumably because they lack interest in the subject and the syllabusitself. Thisresearch is carried out to study the learning attitude in physics and challenges towards learning force and motion among Form Four students in Klang. A total of 200 secondary schools students who are taking physics subject from six schools participated in the study. A descriptive research design was employed using survey method to analyse the students’attitude towards learning physics. The findings on the learning attitudestestshowed majority of the students have favourable attitudes in learning physics. However, majority of students hold poor score in physics test, probably due to low science grade obtained by students in ‘Penilaian Pentaksiran Tingkatan 3’ (PT3). Another finding from the data revealed that the nature of topic was found to be the most predominance challenge in learning force and motion among the participants. The findings are beneficial as they can serve as a stepping stone in overcoming the underlying sources of difficulty that impede quality learning of physics. More in depth study is needed to look into this matter with more number of participants including teachers who are teaching physics.